Peningkatan Pemahaman Konsumen Mengenai Gugatan Perwakilan Kelompok dalam Mewujudkan Perlindungan Konsumen - Suwandono, Agus; Agus Suwandono; Deviana Yuanitasari; Hazar Kusmayanti (FKIP UKI TORAJA, 2025)
The Resolution of consumer disputes involving many consumers will be effective and efficient if carried out jointly through a class action mechanism. Class action is generally a lawsuit filed by a number of people who have the same interests and the same legal events and legal basis. The Objective of this community services is to increase consumer understanding of class action lawsuits in consumer protection law. The approach used in this community service is legal counseling using a participatory action research (PAR) approach. The results of this community service have increased consumer and public understanding of class action lawsuits in consumer protection. The understanding of consumers regarding class action lawsuits is expected to provide consumer with an effective and efficient means of resolving disputes, in addition to filling lawsuits individually. The increased understanding of consumer regarding class action lawsuits is expected to raise awareness and understanding among consumers, thereby realizing consumer protection.